Novel hybrid nanocarbons/poly(dimethylsiloxane) composites based chemiresistors for real time detection of hazardous aromatic hydrocarbons. (April 2016) - Mondal, R.K.; Dubey, K.A.; Bhardwaj, Y.K.; Varshney, L.
Abstract: Hybrid nanocarbons have been reported to have synergetic advantages in several mechanical and electrical applications. However, little is understood how two geometrically different nanocarbons can affect the response of a chemiresistive sensor. The study reports development of poly(dimethylsiloxane) (PDMS)/carbon nanotube (CNT) and nanocarbon black based novel chemiresistive sensors through a solvent free route. These PDMS based sensors demonstrated high sensitivity and reversible response against benzene, toluene, ethyl benzene and xylene (BTEX) under dynamic flow as well as under static vapour conditions. It was found that the sensing response had a strong correlation with the BTEX-PDMS interaction parameters ( χ 12 ). However, such dependence was not observed at 3 wt% loading of CNT, due to CNT induced changes in the diffusion behavior of BTEX. CNT loading affected detection of each analyte differently; though, the principle component analysis using an array of four chemiresistors with different CNT content demonstrated distinct pattern only for benzene. Intriguingly, the sensitivity and the temperature coefficient of resistance of chemiresistors decreased; whereas, the detection range increased considerably with addition of CNT.